A proposal for a CT driven classification of left colon acute diverticulitis - Sartelli, Massimo; Moore, Frederick A; Ansaloni, Luca; Di Saverio, Salomone; Coccolini, Federico; Griffiths, Ewen A; Coimbra, Raul; Agresta, Ferdinando; Sakakushev, Boris; Ordoñez, Carlos A; Abu-Zidan, Fikri M; Karamarkovic, Aleksandar; et al. (World journal of emergency surgery, 2015)
Computed tomography (CT) imaging is the most appropriate diagnostic tool to confirm suspected left colonic diverticulitis. However, the utility of CT imaging goes beyond accurate diagnosis of diverticulitis; the grade of severity on CT imaging may drive treatment planning of patients presenting with acute diverticulitis. The appropriate management of left colon acute diverticulitis remains still debated because of the vast spectrum of clinical presentations and different approaches to treatment proposed. The authors present a new simple classification system based on both CT scan results driving decisions making management of acute diverticulitis that may be universally accepted for day to day practice.